2013
DOI: 10.1016/j.molcel.2013.04.027
|View full text |Cite
|
Sign up to set email alerts
|

JAV1 Controls Jasmonate-Regulated Plant Defense

Abstract: Plants evolve effective mechanisms to protect themselves from environmental stresses and employ jasmonates as vital defense signals to defend against insect attack and pathogen infection. Jasmonates are also recognized as an essential growth regulator by which diverse developmental processes are mediated. Despite substantial research, there are no key signaling components reported yet to control jasmonate-regulated plant defense independent of developmental responses. We identify JAV1, a key gene in the jasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
139
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 44 publications
5
139
1
1
Order By: Relevance
“…A transient expression assay using Arabidopsis mesophyll protoplasts reveals that, except for VQ1, VQ10, VQ22, VQ25, and VQ27, all members of the Arabidopsis VQ family facilitate either transcriptional activation or repression (Li et al, 2014), likely through the binding of specific transcription factors to cis-elements or other coregulators. In agreement with this, genome-wide profiling demonstrated that VQ21 and VQ22 regulate numerous defenseresponsive genes in the SA-and JA-mediated signaling pathway, respectively (Andreasson et al, 2005;Hu et al, 2013a). This notion is further supported by the nuclear localization of some VQ proteins fused with GFP.…”
Section: Mode Of Action Of Vq Proteinssupporting
confidence: 70%
See 4 more Smart Citations
“…A transient expression assay using Arabidopsis mesophyll protoplasts reveals that, except for VQ1, VQ10, VQ22, VQ25, and VQ27, all members of the Arabidopsis VQ family facilitate either transcriptional activation or repression (Li et al, 2014), likely through the binding of specific transcription factors to cis-elements or other coregulators. In agreement with this, genome-wide profiling demonstrated that VQ21 and VQ22 regulate numerous defenseresponsive genes in the SA-and JA-mediated signaling pathway, respectively (Andreasson et al, 2005;Hu et al, 2013a). This notion is further supported by the nuclear localization of some VQ proteins fused with GFP.…”
Section: Mode Of Action Of Vq Proteinssupporting
confidence: 70%
“…Wounding also triggered the degradation of VQ22 in the wild type but not in coronatine insensitive1 (coi1) mutant plants. These results demonstrate that jasmonate or wounding triggers the degradation of VQ22 via the 26S proteasome pathway in a COI1-dependent manner (Hu et al, 2013a). The degradation of VQ22 upon insect attack or pathogen infection likely releases its inhibitory role on positive effectors of plant defense responses (such as WRKY transcription factors).…”
Section: Regulation Of Vq Proteinsmentioning
confidence: 77%
See 3 more Smart Citations